Long-term follow-up after treatment of coronary in-stent restenosis with a paclitaxel-coated balloon catheter - Scheller, Bruno; Haghi, Dariusch (JACC Cardiovascular interventions, 2012)
This study presents long-term clinical follow-up, including binary restenosis rate and major adverse cardiovascular events, of the PACCOCATH-ISR (Treatment of In-Stent Restenosis by Paclitaxel Coated PTCA Balloons) I and II trial. The PACCOCATH-ISR trial was a first-in-human study with a drug-coated balloon catheter and the first study for the treatment of coronary ISR with a drug-coated balloon. So, far no long-term follow-up data have been presented. This study enrolled 108 patients in a randomized, double-blinded multicenter trial on the efficacy and safety of a paclitaxel-coated balloon (3 μg/mm2 balloon surface; PACCOCATH [Bayer AG, Germany]) compared with an uncoated balloon. The main inclusion criteria were a diameter stenosis of ≥70% and <30-mm length with a vessel diameter of 2.5 to 3.5 mm. The primary endpoint was angiographic late lumen loss in-segment after 6 months. Combined antiplatelet therapy was continued only for 1 month followed by treatment with aspirin alone. During a follow-up of 5.4 ± 1.2 years, the clinical event rate was significantly reduced in patients treated with the drug-coated balloon (major adverse cardiovascular events: 59.3% vs. 27.8%, p = 0.009), which was mainly driven by the reduction of target lesion revascularization from 38.9% to 9.3% (p = 0.004).